The chemistry, availability and mobility of molybdenum in Colorado soils - Vlek, Paul L. G., author; Lindsay, Willard L., advisor (Colorado State University. Libraries, 1975)
The purpose of this study was to investigate the impact of molybdenum contamination in irrigation water on soils and pastures in Colorado. The chemistry, availability and mobility of Mo was studied in the laboratory, greenhouse, and field. These results were incorporated into a dynamic computer simulation model that predicts Mo accumulation in forages. Solubility diagrams were constructed from thermodynamic data for naturally occurring molybdenum minerals. The solubility of molybdenum in selected Colorado soils was compared with that predicted by the solubility diagrams. Molybdenum minerals were found to control the solubility of Mo in only one of the thirteen soils studied. Addition of wulfenite (PbMoO4), the most stable Mo mineral, raised the Mo solubility to conform to the solubility isotherm of wulfenite in soils. In the remaining twelve soils the solubility of Mo was controlled by specific adsorption processes, and changed with the degree of Mo saturation and pH. The Freundlich adsorption isotherm was extended with a pH term to describe the solubility relationship of Mo in soils. The availability of Mo in soils was studied in both greenhouse and field. Additions of Na2MoO4 to soils increased the uptake of Mo by alfalfa, clover, and bluegrass; the uptake increased with alkalinity. Water-extractable or (NH4)2CO3-extractable soil Mo accurately predicted the concentration of Mo in alfalfa grown on neutral and alkaline soils (r= .97 in the greenhouse, and r= .85 in the field). The information obtained in the laboratory and greenhouse studies was used to develop a computer model to simulate the impact of high-Mo irrigation water on soils and forages. The model used simulated daily growth of alfalfa under climatic conditions typical for Colorado. Changes in the Mo content of the rhizosphere were evaluated daily by considering inputs from irrigation water and losses from leaching and plant uptake. The impact of Mo contamination on forage was shown to depend on the quality and amount of irrigation water applied to the field, as well as on the type and leachability of the soil. Toxic levels of Mo were predicted for alfalfa grown on a clayey soil after 15 years of irrigation with 300 mm of water containing 100 ppb Mo. It was demonstrated that most soils irrigated with water containing more than 25 ppb Mo will eventually produce toxic forages.
Covers not scanned.
Keywords: Soils -- Molybdenum content